Intestinal permeability is increased in bronchial asthma. Issue 3 (20th February 2004) - Hijazi, Z; Molla, A M; Al-Habashi, H; Muawad, W M R A; Molla, A M; Sharma, P N
Abstract : Background: Increased intestinal permeability has been reported in one study of adult asthmatics. Aim: To determine whether children with asthma have altered intestinal permeability. Methods: Thirty two asthmatic children, and 32 sex and age matched controls were recruited. The dual sugar (lactulose and mannitol) test was used to evaluate intestinal permeability, and the percentage of ingested lactulose (L) and mannitol (M) in the urine, and the L:M ratio were determined. All patients were skin prick tested for common aeroallergens, and specific IgE to some food items was determined. Results: The median value of L in asthmatic children (2.29, IQR 0.91–4.07) was significantly higher than that in controls (0.69, IQR 0.45–1.08), and that of M was almost similar. The ratio L:M was significantly higher in asthmatic children (0.20, IQR 0.11–0.40) than in controls (0.06, IQR 0.04–0.09). Intestinal permeability did not correlate with eczema, inhaled steroids, positive skin prick test to aeroallergens, or severity of asthma. Conclusions: Intestinal permeability is increased in children with asthma, suggesting that the whole mucosal system may be affected.